The Neocomian of Chachahuén (Mendoza, Argentina): evidence of a broken foreland associated with the Payenia flat-slab - Sagripanti, Lucía (2014)
Isolated marine sedimentary Lower Cretaceous deposits crop out in the foreland of the Neuquén Basin, west-central Argentina. They are the result of an anomalous uplift of the Sierra de Chachahuén in the far foreland region. These outcrops are assigned to the Agrio Formation based on their rich fossil contents. In particular, the study reveals a unique outcrop of continental facies along the eastern proximal margin of the basin that were known only from core wells, and constitutes the first exposed evidence at the surface. These deformed deposits are 70 km from the Andean orogenic front and present 2 km of local uplift produced by high-angle basement reverse faults that reactivated a previous Early Mesozoic rift system. The increase in compression was related to the decrease in the subduction angle. This fact, together with the expansion of the magmatic arc, controlled the Chachahuén calc-alkaline Late Miocene volcanic centre and the uplift of the Mesozoic deposits in the foreland. This broken foreland was associated with localized heating of the Miocene volcanic centre that produced the rising of the brittle-ductile transitions. This fact weakens the foreland area, which was broken by compression during the development of the Payenia flat-slab.